Analisa Mesin Pengering Makanan Food Dehidrator Menggunakan Sensor Thermostat Berbasis Hybrid - Pinandita, Satria; Supari, Supari; Saputra, Dian Nova; Al Amin, Anggara Fuad (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2024)
The process of drying food is done in the traditional way, by drying it in the hot sun, but the traditional drying method makes the food unhygienic. Several factors can influence the drying results of food ingredients, including temperature and drying time. Using optimal drying temperatures and times can reduce the level of damage caused by the drying process. This research aims to obtain an analysis of a food dehydrator drying machine using a hybrid-based thermostat sensor that can optimally condition the temperature and time factors in the drying process, the hyfood dehydrator machine system uses a dehumidification method, there is a heat recovery mechanism that recycles heat to open new air, thus saving 60-70% of fresh air preheating energy consumption. Hot air moving in the room dries the material. It is known that the test result data was analyzed by calculating the accuracy values, down to the relative distance values. The results of the comparison process are used as validation of the output values ??produced by the temperature measuring instrument. The measurement results of the Digital Thermostat Sensor are in accordance with the datasheet and have a high level of accuracy. So the Digital Thermostat Sensor measuring instrument can be used as a measurement tool. With an internal fan, thermostat, and time settings on this device, you only need to set the right heat according to the type of food you want to dry. The shelves in the cupboard consist of drying trays that can maximize the drying process